TRUE POLAR WANDER DURING THE PERMO-TRIASSIC - Marcano M.C.; Van der Voo R.; Mac Niocaill C. (My University, 1999)
The apparent polar wander path for the Pangea supercontinent is about 35° long for the interval of 295-205Ma, which means that in that interval Pangea rotated over an angle of 35° with respect to the rotation axis about an Euler pole located at the equator. If the rest of the world, largely comprised of the Panthalassa Ocean, rotated about the same Euler pole in the same sense as Pangea, then a good case can be made that true polar wander occurred during the Permo-Triassic. In contrast, if the Panthalassa Ocean moved in a sense opposite to that of Pangea, then true polar wander is not likely to have occured. In the latter case, convergence between Panthalassa and Pangea would have led to subduction of large amounts of ocean crust under the leading edge of Pangea. We have examined the geology of Pangea's leading edge for evidence of such subduction, in the form of Permo-Triassic plutonism, andesitic volcanism and deformation. No such evidence was generally found, except for areas very close to the Euler pole in the western U.S.A. and in displaced terranes that also were in near-equatorial paleolatitudes at the time. We conclude that true polar wander has most likely occurred during the Permo^Triassic at a rate of about 0.4 per million years.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая